2012
DOI: 10.1021/ja212217j
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Enantioselectivity during Allylic Substitution Reactions Catalyzed by Metallacyclic Iridium Complexes

Abstract: In depth mechanistic studies of iridium catalyzed regioselective and enantioselective allylic substitution reactions are presented. A series of cyclometallated allyliridium complexes that are kinetically and chemically competent to be intermediates in the allylic substitution reactions was prepared and characterized by 1D and 2D NMR spectroscopies and solid state structural analysis. The rates of epimerization of the less thermodynamically stable diastereomeric allyliridium complexes to the thermodynamically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 40 publications
(105 reference statements)
0
41
0
Order By: Relevance
“…16 Thus, we studied the oxidative addition of allylic trifluoroacetates, which contain a good leaving group and were shown to add to Ir(I) complexes of a cyclometalated phosphoramidite. 18 In particular, the reactions of the linear and branched isomers of the phenalkyl-substituted allylic trifluoroacetates 8 and 9 with the Ir(I) ethylene adduct 5 were studied. These reactions occurred to form an equilibrium mixture of unreacted 5 and two diastereoisomers of allyliridium complexes 3c .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Thus, we studied the oxidative addition of allylic trifluoroacetates, which contain a good leaving group and were shown to add to Ir(I) complexes of a cyclometalated phosphoramidite. 18 In particular, the reactions of the linear and branched isomers of the phenalkyl-substituted allylic trifluoroacetates 8 and 9 with the Ir(I) ethylene adduct 5 were studied. These reactions occurred to form an equilibrium mixture of unreacted 5 and two diastereoisomers of allyliridium complexes 3c .…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Mechanistic studies on reactions catalyzed by these iridium complexes have revealed the resting state of the catalyst, the origins of enantioselection, and the importance of cyclometalation to generate the active catalyst. 1518 However, mechanistic studies of reactions catalyzed by iridium complexes of triphenylphosphite, the first system shown by Takeuchi to give branched products from linear allylic carbonates 1921 are limited. A cyclometalated species was proposed to be the active catalyst, but this species was never observed directly and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…8a The relative configuration of the product and iridium catalyst shows that the allylic substitution step of the functionalization sequence occurs with the same stereoselectivity as previously reported substitutions of allylic carbonates. 7c,15 Previously reported mechanistic studies from our group on iridium catalyzed allylic substitution reactions 7d,16 have shown that the reaction occurs by a highly diastereoselective oxidative addition of an allylic benzoate to an iridium complex 1 , followed by attack of the nucleophile onto the allyl ligand from the side opposite to the metal for all of the nucleophiles in the current study. This nucleophilic attack is a faster than the η 3 -η 1 -η 3 isomerization of the allyl complex.…”
Section: Resultsmentioning
confidence: 57%
“…[8,9] Thelow acidity of the a hydrogen atoms of aliphatic esters and the instability of the ester-derived enolates make the allylation of ester enolates challenging.Stoichiometric strong bases are required to form the enolates in situ without selfcondensation, substrates that bear base-sensitive functionalities (for example,a na cetoxy group) are not tolerated, and Claisen condensation between the ester products and the enolates can lead to side products.F inally,c yclopropanation has been shown to compete with the allylation process when palladium catalysts are used. [11] Thea llylation of silyl ketene acetals containing gemdialkyl groups would be particularly valuable because the resulting enantioenriched a-allyl esters containing aq uaternary a carbon atom and at ertiary b stereocenter are inaccessible by asymmetric Michael addition or asymmetric hydrogenation of the a,b-unsaturated esters.F urthermore, the enantioselective allylation of stabilized malonate-type nucleophiles,followed by fragmentation (desulfonylation and decarboxylation), would not afford these highly substituted products. Iridium complexes [Ir] (Scheme 1) developed in our research group could catalyze this proposed transformation because they enable enantioselective allylic substitution reactions with various nucleophiles under relatively neutral conditions,w ithout competing formation of cyclopropanes.…”
Section: Catalyticasymmetricallylicsubstitutionwithenolatesformsmentioning
confidence: 99%
“…Iridium complexes [Ir] (Scheme 1) developed in our research group could catalyze this proposed transformation because they enable enantioselective allylic substitution reactions with various nucleophiles under relatively neutral conditions,w ithout competing formation of cyclopropanes. [11] Thea llylation of silyl ketene acetals containing gemdialkyl groups would be particularly valuable because the resulting enantioenriched a-allyl esters containing aq uaternary a carbon atom and at ertiary b stereocenter are inaccessible by asymmetric Michael addition or asymmetric hydrogenation of the a,b-unsaturated esters.F urthermore, the enantioselective allylation of stabilized malonate-type nucleophiles,followed by fragmentation (desulfonylation and decarboxylation), would not afford these highly substituted products. [12] Herein we report the enantioselective allylation of silyl ketene acetals catalyzed by am etallacyclic iridium complex (Scheme 1) to form the allylated aliphatic esters with high regio-and enantioselectivity under mild conditions.Owing to the versatility of the ester functionality in organic synthesis, these products are readily transformed into primary alcohols, carboxylic acids,amides,isocyanates,carbamates,tetrahydrofuran (THF) derivatives,a nd g-butyrolactone derivatives without erosion of enantiomeric purity.We began our studies on the enantioselective allylic substitution of aliphatic silyl ketene acetals by examining the reaction between cinnamyl methyl carbonate and ketene acetal 2a in the presence of as eries of metallacyclic iridium complexes containing various aryl substituents on the chiral ligand (Table 1, entry 1-4).…”
mentioning
confidence: 99%